Factors Affecting Training Effectiveness of Extension Personnel in PAMETI, Punjab - Anshuman, Jyotishree; Kaur, Rupinder; Rampal, Vipan Kumar; Jayasingh, Debi Kalyan (Indian Journal of Extension Education, 2024)
This study was executed for identifying the key factors that impact the effectiveness of training programs under the aegis of ex-post facto research design in 2023-24 timeline. The sample comprised trainees participating in a range of competency development training programs organized by the “Punjab Agricultural Management and Extension Training Institute” (PAMETI) during 2017–2018. Five training programs were selected in total with 24 trainees from each program chosen through random sampling constituting the sample of 120 respondents.Majority of trainees were predominantly perceived to fall within the moderate category regarding training effectiveness. Factors accounted for 64.38% of the variation in training effectiveness among the trainees. Achievement motivation, job performance and satisfaction, self-attitude and mass media exposure of trainees were found to substantially influence the variation in training effectiveness.